Improving Communication Skills Through Psychology: A Qualitative Study on Active Listening, Cultural Sensitivity, and Role-Playing Techniques among Undergraduate Students - Mehrad, Aida (Academic Journal of Da'wa and Communication, 2025)
Effective communication is a fundamental aspect of human interaction, impacting personal relationships, academic engagement, and professional success. In psychology education, it is crucial to equip students not only with theoretical knowledge but also with practical communication strategies that are adaptable to various cultural and social contexts. This study explores how undergraduate psychology students perceive the role of communication in their personal, academic, and future professional lives, as well as the impact of a semester-long course titled "Communication in Psychology" on their skill development. A total of 29 students from the University of American College Skopje participated in the research, reflecting on their experiences through open-ended survey questions after completing the course. Qualitative content analysis was used to identify recurring themes in their responses. The findings suggest that students perceive communication as crucial for fostering empathy, articulating ideas effectively, and avoiding misunderstandings. They reported improvements in active listening, interpreting nonverbal cues, and engaging in culturally sensitive dialogue. Practical exercises, such as role-playing and mock interviews, were efficient in helping students internalize key concepts. Students also highlighted the importance of patience, empathy, and creating nonjudgmental environments to foster meaningful interactions. This study highlights the importance of communication-focused training within the psychology curriculum, underscoring its transformative impact on enhancing self-awareness, intercultural competence, and interpersonal effectiveness—all essential skills for future professionals working in complex, multicultural environments.